Highly Efficient and Convenient Access to Phosphinates via CHCl3‐Assisted Direct Phosphorylation between R2P(O)H and ROH by Phosphonium Salt Catalysis. Issue 20 (8th May 2020) - Yu, Xiaojun; Zhang, Song; Jiang, Zhiyu; Zhang, Hong‐Su; Wang, Tianli
Abstract : A mild, efficient, convenient and scalable method to synthesize phosphinates via direct phosphorylation between R2 P(O)H and ROH was developed. All aromatic substrates completed this transformation with excellent yields (up to 98 %), and preliminary mechanistic studies suggest that a carbene‐involving process from CHCl3 to CH2 Cl2 facilitates the phosphorylation. Abstract : A mild, efficient, convenient, and scalable method to synthesize phosphinates via direct phosphorylation between R2 P(O)H and ROH was developed. Preliminary mechanistic studies suggest that a carbene‐involving process from CHCl3 to CH2 Cl2 facilitates the phosphorylation.